“Nobody Tells us what to Write about”: The Disinformation Media Ecosystem and its Consumers in the Czech Republic - Štětka, Václav; Mazák, Jaromír; Vochocová, Lenka (Javnost-The Public, 2021)
The rise of digital platforms has provided an opportunity for an unprecedented expansion of the public sphere; however, the recent proliferation of online disinformation, automated propaganda as well as hate speech has substantially hampered their potential to become an instrument for more egalitarian and participatory communication in a democratic society. In many countries, the ascent of right-wing populism in recent years has been associated with the establishing of an alternative information environment that includes a variety of fringe news websites that frequently engage in spreading rumours, hoaxes and conspiracy theories. Attempting to fill the gap in the scholarship that predominantly tends to focus on the US and Western European political and media context, this article aims to map the disinformation ecosystem and its audiences in the Czech Republic, a country where the online disinformation scene has been particularly active in recent years. Following an outline of the evolution of the Czech media system over the course of the last three decades, this study utilises data from the 2018–2020 Digital News Report surveys to provide empirical insights into the characteristics of the consumers of the most prominent disinformation news websites in the Czech Republic. In conclusions, the paper evaluates the challenges these new patterns of (dis)information consumption pose for the post-transition public sphere in the Czech Republic, especially in context of the processes of democratic deconsolidation and the rise of illiberalism.